Novel reverse radioisotope labelling experiment reveals carbon assimilation of marine calcifiers under ocean acidification conditions. Issue 6 (11th May 2020) - Nishida, Kozue; Chew, Yue Chin; Miyairi, Yosuke; Hirabayashi, Shoko; Suzuki, Atsushi; Hayashi, Masahiro; Yamamoto, Yuzo; Sato, Mizuho; Nojiri, Yukihiro; Yokoyama, Yusuke
Abstract: Ocean acidification by anthropogenic carbon dioxide emissions is projected to depress metabolic and physiological activity in marine calcifiers. To evaluate the sensitivity of marine organisms against ocean acidification, the assimilation of nutrients into carbonate shells and soft tissues must be examined. We designed a novel experimental protocol, reverse radioisotope labelling, to trace partitioning of nutrients within a single bivalve species under ocean acidification conditions. Injecting CO2 gas, free from radiocarbon, can provide a large contrast between carbon dissolved in the water and the one assimilated from atmosphere. By culturing modern aquifer organisms in acidified seawater, we were able to determine differences in the relative contributions of the end members, dissolved inorganic carbon (DIC) in seawater and metabolic CO2, to shell carbonate and soft tissues. Under all p CO2 conditions (463, 653, 872, 1, 137 and 1, 337 μatm), radiocarbon (Δ 14 C) values of the bivalve Scapharca broughtonii shell were significantly correlated with seawater DIC values; therefore, shell carbonate was derived principally from seawater DIC. The Δ 14 C results together with stable carbon isotope (δ 13 C) data suggest that in S. broughtonii shell δ 13 C may reflect the kinetics of isotopic equilibration as well as end‐member contributions; thus, care must be taken when analysing end‐member contributions by a previous method using δ 13 C. The insensitivity of S. broughtonii to perturbations in p CO2 up to at least 1, 337 µatm indicates that this species can withstand ocean acidification. Usage of radioisotope to dope for tracer experiments requires strict rules to conduct any operations. Yet, reverse radioisotope labelling proposing in this study has a large advantage and is a powerful tool to understanding physiology of aquifer organisms that can be applicable to various organisms and culture experiments, such as temperature, salinity and acidification experiments, to improve understanding of the proportions of nutrients taken in by marine organisms under changing environments. 概要: 人為起源の二酸化炭素排出に伴い、地球温暖化とともに海洋酸性化が進行している。海洋酸性化は海洋生物の生理や代謝に影響を及ぼす可能性があり、海洋生物の耐性を評価していく上で貝殻や軟体部形成に寄与する炭素源を理解することが求められる。 本研究では、新たな炭素源推定法として放射性炭素同位体（Δ 14 C）を活用した「リバースラジオアイソトープ標識法」を提案した。二枚貝類アカガイの海洋酸性化実験個体を用いて炭素源推定を行い、殻や軟体部形成への海洋酸性化影響を評価した。本研究の標識法では、酸性化環境を調製するために海水に添加する化石燃料起源の二酸化炭素ガスをトレーサーとして用いる。海水が酸性化するほど、海水の溶存無機炭素（DIC）は低いΔ 14 C値を示す。そのため、この海水の同位体傾斜をもとに、殻や軟体部への海水のDICやエサの寄与率を推定できる。 本標識法を用いた飼育実験の結果、殻のΔ 14 Cは、いずれの実験区でも海水のDICとほぼ同一の値を示し、貝類の石灰化には海水のDICが主な供給源であることが分かった。殻の炭素安定同位体比（δ 13 C）は、海水のDICのδ 13 Cに比べて変化が小さく、速度論的同位体効果といった同位体分別が関わっていると予想される。したがって、貝類の場合、従来法のδ 13 Cによる炭素源推定法では生物効果が含まれてしまうため、石灰化の炭素源推定には殻のΔ 14 C解析が有効と考えられる。 本標識法は、管理区域指定が必要な 14 C標識物質ではなく、天然に存在する二酸化炭素ガスを活用しているため、安全、安価かつ汎用性の高い手法である。海洋生物の殻形成・軟体部形成にかかわる炭素循環を明らかにする上で重要な指標であり、多様な海洋生物で様々な生物実験系（水温、塩分、酸性化実験など）での応用が期待される。